STUDI TENTANG DAMPAK GREEN CAMPUS TERHADAP KESADARAN LINGKUNGAN MAHASISWA DI UIN RADEN INTAN LAMPUNG - Rangga Bagaskara, Figo; Angga Pratama; Bagas Armayoga; Ali Murtadho; Baharudin; Ikhsan Mustofa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to evaluate the impact of the Green Campus programme on students' environmental understanding, attitudes and behaviours, as well as identify factors that influence its successful implementation at UIN Raden Intan Lampung. The research used a qualitative approach with a case study method, involving 5-10 students as subjects. Data were collected through in-depth interviews, Focus Group Discussions (FGDs), and participatory observations, then analysed through transcription, encoding, theme identification, triangulation, and interpretation of findings. The results showed that the Green Campus programme significantly contributed to increasing students' environmental awareness and behaviour. Supporting factors include personal awareness, campus policy, social interaction, personal experience, and extracurricular activities. Support from lecturers, campus officials, and educational materials also play an important role, although effectiveness can be improved through practical training and the utilisation of technology. The programme not only changes students' behaviour on campus, but also influences their actions in daily life.